Intervensi dalam Mengendalikan Ketidakstabilan Glukosa Darah pada Asuhan Keperawatan Pasien Diabetes Melitus Tipe 2 di Masyarakat ; Literatur Review - Israfil (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: This study aims to identify various types of interventions in controlling unstable blood glucose levels in the care of type 2 diabetes mellitus patients in the community. Method: literature review research design, literature sources are research articles on the Google Scholar or Google Cendikia database, and Researchgate. The literature search used the keywords